(untitled) (Chemical Engineering Research Bulletin, 2020)
Since some previous years, reactive extraction has become more attractive and competitive technique for the separation and purification of lower carboxylic acids from fermentation broth as well as from dilute aqueous streams. This paper shows the results of investigation of reactive extraction of lactic acid (LA) from an aqueous solution using the synergistic mixture of the extractants (TOA (tri-n-octylamine) and TOMAC (Tri-n-octylmethylammonium chloride)) and a non-toxic and biocompatible green solvent (soybean oil). Three-level Box-Behnken design (BBD) under response surface methodology (RSM) was opted for the experimental design and to interpret the mutual effect of seven independent process parameters on the LA distribution coefficient (KD). The maximum values of LA distribution coefficient (KD=2.51) and its extraction efficiency (ηη=71.5%) were obtained for the optimum values of various process parameters such as 0.02 [M] initial LA concentration (CC1), 0.5 (v/v) extractant ratio (α), 28.66% (v/v) mixed extractants concentration (ψ), 2 (v/v) phase ratio (φ), 270C temperature (T), 102 rpm stirring speed (ω), and 63 mincontact time (τ). This present investigation will provide a noble discussion on LA reactive extraction using green solvent and on various influencing process parameters for gaining the enhanced value of LA distribution coefficient (KD). Chemical Engineering Research Bulletin 21(2019) 20-35